Pedobarography as a prophylactic test in type 2 diabetes - Karpińska, Anna; Szewczyk, Maria T. (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2019)
Along with the progress of civilisation, the number of people suffering from type 2 diabetes increases. Abnormal glucose metabolism results in complications within the nervous and vascular system. The most common complications of diabetes are microangiopathies and macroangiopathies. Improper functioning of the nervous system and damage to blood vessels can lead to the development of diabetic foot syndrome. Patients, due to disturbed sensation, are most often unaware of the foot injury they have suffered from and a hard wound develops on the ground of a small wound, which, if infected, may lead to limb amputation. Prevention is an extremely important element. Patients with diabetes should have adequate knowledge of how to manage the disease and how to care for the feet. The precise tool used to assess the pressure distribution on the plantar side of the foot is the pedobarograph.